DEVELOPMENT OF AUTOMATED INTELLIGENT DRIP IRRIGATION SYSTEM - A.U.Djalilov; I.K.Gayipov; R.K. Kenesbaev; Zh.Abdunabiyev; A.Saidov; M.Axmedov (Galaxy International Interdisciplinary Research Journal, 2022)
The need for water for irrigation of agricultural crops in our country is growing from year to year, and this situation may cause current problems in the future. Therefore, for the rational use of available water resources in agriculture, an effective system that meets modern requirements is needed. A modern drip irrigation system significantly reduces water consumption compared to traditional methods.This article proposes an intelligent automated drip irrigation system for irrigating crops, in which a smartphone first takes a picture of the soil, calculates its moisture level, and from time to time transmits data to the microcontroller via a GSM module. The microcontroller decides whether the crops need to be watered or vice versa and sends the field status to the farmer's mobile phone. The intelligent system was tested in cotton fields for three months. Experience has shown that irrigation of cotton using the developed intelligent system saves about 42% and 15% of water consumption compared to traditional and drip irrigation methods.